Granulocyte–macrophage colony‐stimulating factor (GM‐CSF) as a therapeutic target in psoriasis: randomized, controlled investigation using namilumab, a specific human anti‐GM‐CSF monoclonal antibody. (2nd November 2018) - Papp, K.A.; Gooderham, M.; Jenkins, R.; Vender, R.; Szepietowski, J.C.; Wagner, T.; Hunt, B.; Souberbielle, B.; ,
Summary: Background: The relevance of granulocyte–macrophage colony‐stimulating factor (GM‐CSF) in the management of psoriasis has not been studied previously. GM‐CSF is important in the initiation and maintenance of chronic inflammatory processes. Objectives: To investigate the clinical use of GM‐CSF neutralization by evaluating the efficacy and safety of namilumab (AMG203), a monoclonal antibody GM‐CSF inhibitor, in patients with moderate‐to‐severe plaque psoriasis. Methods: A phase II, multicentre, randomized, double‐blind, placebo‐controlled, parallel‐group, dose‐finding, proof‐of‐concept study (NEPTUNE) was conducted. Four doses of namilumab (20, 50, 80 and 150 mg, via subcutaneous injection) were compared with placebo. Assessment of the primary end point – the proportion of patients achieving ≥ 75% reduction in Psoriasis Area and Severity Index (PASI 75 treatment response) – was performed at week 12. Exploratory investigation at the tissue level was conducted in a subset of the overall study population. The trial was registered with the number NCT02129777. Results: In total, 122 patients were enrolled and 106 (86·9%) completed the double‐blind treatment; 16 (13·1%) prematurely discontinued study medication. Serum concentration–time profiles were as expected for subcutaneous delivery of an IgG1 monoclonal antibody, and exposure increased proportionally with dose elevation. The number of patients showing PASI 75 treatment response at week 12 was low in all groups; no significant difference was recorded in this end point between placebo and any namilumab group. Similar outcomes were recorded for other clinical study end points. Moreover, no significant treatment‐related changes from baseline were observed in laboratory investigations of cell types or subpopulations, or cytokines relevant to inflammatory pathways in psoriasis. Conclusions: GM‐CSF blockade is not critical for suppression of key inflammatory pathways underlying psoriasis. Abstract : What's already known about this topic? Blockade of granulocyte–macrophage colony‐stimulating factor (GM‐CSF) signalling is effective in rheumatoid arthritis. Potential relevance for psoriasis has been indicated by the presence of GM‐CSF in psoriasis‐related skin blister fluid and the serum of patients with psoriasis, and also by elevated expression in psoriatic skin lesions. What does this study add? This is the first clinical investigation into the efficacy and safety of an anti‐GM‐CSF antibody in plaque psoriasis. This study provides no evidence of benefit for GM‐CSF neutralization in the treatment of plaque psoriasis. Safety profiles were comparable in the placebo and anti‐GM‐CSF treatment groups, and no incidences of pulmonary alveolar proteinosis or clinically significant changes in lung function were recorded throughout the short‐term duration of study treatment. Overall, the findings point to key differences in the role of GM‐CSF in the pathogeneses of psoriasis and rheumatoid arthritis. Linked Comment: Crowley. Br J Dermatol 2019; 180 :1286–1287 . Plain language summary available online Respond to this article